Recent Advancements in Microfluidic Circulating Tumor Cell Sorting Devices - Jamrus, Muhammad Asyraf; Ahmad, Mohd Ridzuan (ELEKTRIKA- Journal of Electrical Engineering, 2024)
In recent years, there has been significant advancement in the creation of microfluidic devices for sorting circulating tumor cells (CTCs), which has transformed the field of cancer diagnosis. This study offers a thorough examination of the most recent developments in microfluidic technology created for accurate and effective isolation of CTCs from intricate biological materials. The integration of active and passive techniques on microfluidic systems has resulted in advancements in sensitivity, specificity, and therapeutic relevance. Advanced methods like acoustofluidic and microfluidic dielectrophoresis can be used for specific capture of circulating tumor cells (CTCs), while simpler approaches such as size-based filtering and deterministic lateral displacement are suitable for various sample types. Hybrid methods, which blend the advantages of active and passive principles, have become a potential strategy for enhancing CTC isolation efficiency. These advancements have far-reaching implications for liquid biopsy applications, making it easier to monitor cancer progression, detect it early, and evaluate responses to treatment without intrusive procedures.